2008
DOI: 10.1002/ptr.2662
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antihyperalgesic effect of curcumin on formalin‐induced orofacial pain in rat

Abstract: The present study was planned to evaluate the role of curcumin in the formalin-induced orofacial pain in rats that mimics typical human orofacial pain. Adult Wistar rats of either sex received an injection of 50 microL of 5% v/v subcutaneous formalin injection into one vibrissal pad and consequent facial grooming behavior was monitored. Animals exhibited two distinct periods of nocifensive grooming: (a) an acute phase lasting 0-6 min; and (b) a tonic phase lasting 6-45 min. The analgesic response of curcumin w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
44
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 26 publications
(28 reference statements)
5
44
0
1
Order By: Relevance
“…Clinical trials have shown curcumin to be safe at daily dose [12 g for 3 months [6,20]. Curcumin-mediated suppression of pain and fatigue pathways has been reported extensively in the literature across a spectrum of experimental models [25][26][27][28][29][30][31]. The benefits of curcumin in respect of postoperative pain and fatigue are significant, as shown in our study.…”
Section: Discussionsupporting
confidence: 65%
“…Clinical trials have shown curcumin to be safe at daily dose [12 g for 3 months [6,20]. Curcumin-mediated suppression of pain and fatigue pathways has been reported extensively in the literature across a spectrum of experimental models [25][26][27][28][29][30][31]. The benefits of curcumin in respect of postoperative pain and fatigue are significant, as shown in our study.…”
Section: Discussionsupporting
confidence: 65%
“…In inflammatory pain context, curcumin inhibited overt pain-like behavior in formalin test [40], which has two components. The early phase (0-5 min) dependent on activation of nociceptors through TRPA1 receptors, which are important receptors in inflammatory pain and their increased activity, occurs in O 2…”
Section: Discussionmentioning
confidence: 99%
“…For example, systemic curcumin has been shown consistently to produce significant reductions in the second phase of formalin-induced nocifensive behaviors in animals indicating inhibition of central sensitization. [8][9][10] Curcumin has also shown efficacy in models of neuropathic pain. For example, using the streptozotocin model of diabetic neuropathy curcumin reduced thermal hyperalgesia as well as serum levels of the proinflammatory, pronociceptive cytokine tumor necrosis factor alpha (TNFα).…”
mentioning
confidence: 98%